Composite technology : prepregs and monolithic part fabrication technologies - Lengsfeld, Hauke, 1971-; Lacalle, Javier; Neumeyer, Thomas; Altstädt, V. (Hanser, 2021)
Prepreg materials are pre-impregnated fibers for the manufacture of composite components, and are widely applied in the wind energy and aerospace industries. The properties of these semi-finished products, the type of processing, and the component design collectively play an important role in the quality and suitability for mass production of a fiber composite component. This book provides a holistic approach, showing the influence and mutual interaction of the parameters involved in the production of fiber composite components. "Composite Technology" gives an overview of the current state of prepreg technology, generation, and development as well as their variations and trends. It covers the fundamentals of prepreg preparation and starting materials; processing technology and automation; interactions between construction/design and material and between tooling material and composite components/design; testing of prepreg semi-finished products and components; and typical error patterns. The second edition has been systematically updated; in particular, new developments at manufacturers and processors have been incorporated. The addition of thermoplastic prepregs (TPP) and their production, processing, and testing completes the topic